Effect of sandstone and mudstone thickness on artificial fracturing for hydrocarbon extraction from low-permeability reservoirs - Liu Peigang; Wang Zhelin; Lu Kai; Zhang Zhiqiang (Natural Gas Industry B, 2022)
Hydraulic fracturing of low-permeability continental reservoirs that possess argillaceous interlayers between single sand bodies is poorly understood. In this study, the delta-front-facies, low-permeability sand–mudstone interbedded reservoir of the Ansai district, Ordos Basin, is used as a case study. The reservoir characteristics of different sedimentary microfacies were identified using information from outcrops, drill cores and well logging. Six reservoir physical models of sand–mudstone assemblages were established on the basis of these data. The fracture growth patterns and parameters of the six models were obtained by numerical simulation. Numerical simulation with different fracturing parameters was conducted, to obtain the best parameters for each model to achieve different fracturing effects. The results show that crack size is influenced by the thickness of sandstone and mudstone units, the sandstone to mudstone ratio, and fracturing operation parameters. Sandstone thickness is extremely important in crack propagation. For medium and thick sandstone (3–5 m thick) interbedded with thin mudstone (<0.3 m thick), fracture width and length are large, and longitudinal fractures can pierce mudstone layers. In contrast, for thin sandstone (<1.5 m thick) interbedded with thick mudstone (>0.8 m thick), fractures are small and often restricted to a single sand body, and the mudstone interlayers limit the longitudinal extent of cracks. The six models represent three sedimentary microfacies with different distributions of sandstone and mudstone. Oil well artificial fracture shapes and parameters in different microfacies were visualized through simulation with different models, and match well with data from actual fields We also conducted fracture simulation by changing the fracturing construction parameters to obtain the optimal parameters for different fracturing effects in the models, providing a new understanding of the mudstone interlayers between single sand bodies (>0.3 m thick) and an important basis for oil field construction.